The future of (negative) emissions trading in the European Union - Wilfried Rickels; Alexander Proelß; Oliver Geden; Julian Burhenne; Mathias Fridahl (Kiel Institute for the World Economy (IfW), 2020)
Under the European Union Emissions Trading System (EU ETS), operators must surrender allowances corresponding to the emissions of greenhouse gases (GHG) from their installations. The supply of allowances in the EU ETS decreases linearly and, all else equal, is expected to end around 2057. An earlier cut-off date is likely to follow from the European Council's recent decision that the EU should reach net-zero GHG emissions by 2050. Scenarios published by the European Commission even anticipate a net-negative cap in the EU ETS from 2045 onwards, generated through carbon dioxide (CO2) removals. Upholding emissions trading, in the long run, therefore entails significant use of credits resulting from atmospheric CO2 removal activities. However, in its current form, the ETS Directive does not contain any legal basis for generating CO2 removal credits. Integrating CO2 removal into the EU ETS would, thus, require fundamental amendments of the ETS Directive, waiving the currently mandatory association binding emitting activities to the adoption of emission abatement technologies. The next policy window for such amendments will open in 2021, following the decision on a more ambitious EU 2030 emission reduction target. This conceptual paper explores various design options for integrating negative emissions technologies (NETs) into the EU ETS. We discuss their potential implications for emissions trading at large and address the specificity of bioenergy with carbon capture and storage (BECCS); repealing the provision that installations exclusively using biomass are not covered by the ETS Directive, BE(CCS) installations could in principle fall within the scope of the ETS Directive. Theoretically, it would be possible to consider free allocation of biogenic credits to BE(CCS) installations. Bioenergy operators could avoid having to surrender these biogenic allowances through the use of CCS and instead sell them on the EU ETS market, having implicitly received credits for the removal of CO2 from the atmosphere.
Keywords: K33; Q54; Q58; 330; European Emission Trading; Carbon Dioxide Removal; Negative Emission Technologies